Development of cross-linkable dimeric triarylmethine derivatives with improved thermal and solvent stability for color filters. (February 2018) - Jung, Hyocheol; Kong, Nam Sik; Kim, Beomjin; Lee, Kyu Cheol; Kim, Soon Cheon; Lee, Chan Kyu; Kong, Hoyoul; Jun, Kun; Kim, Jin Chul; Noh, Seung Man; Cheong, In Woo; Park, Jongwook; et al.
Abstract: A new dimeric triarylmethine-based dye, Ac-BTM-DHFMS, substituted with methacrylate groups, was designed and synthesized to improve thermal and chemical stability by using polymerisation of the acrylate cross-linking group. To evaluate the dye in color filter applications, filters were fabricated and evaluated after heat treatment at 230 °C for 1 h, and solvent stability was evaluated after dipping filters for 10 min in isopropyl alcohol (IPA), propylene glycol monomethyl ether acetate (PGMEA), and cyclohexanone. During the thermal stability test, Ac-BTM-DHFMS showed a ΔEab value of 4.21. In the solvent stability test, Ac-BTM-DHFMS showed ΔEab values of 1.0 (IPA), 0.3 (PGMEA), and 0.7 (cyclohexanone), respectively. These ΔEab values of color filter mean that Ac-BTM-DHFMS is thermally and chemically more stable than H-BTM-DHFMS without the methacrylate groups. These results show that Ac-BTM-DHFMS has potential for application as a color filter for blue dyes. Graphical abstract: Highlights: Ac-BTM-DHFMS substituted with methacrylate groups has been designed and synthesized as potential color filter dyes. Ac-BTM-DHFMS showed improved solubility due to twisted molecular structure and bulky methacrylate groups. Cross-linkable group of Ac-BTM-DHFMS make be improved thermal/chemical stability.